Neuropathic pain, antidepressant drugs, and inflammation: a narrative review - Giulia Catalisano; Gioacchina Martina Campione; Giulia Spurio; Alberto Nicolò Galvano; Cesira Palmeri di Villalba; Antonino Giarratano; Antonietta Alongi; Mariachiara Ippolito; Andrea Cortegiani (Journal of Anesthesia, Analgesia and Critical Care, 2024)
Abstract Background Neuropathic pain (NP) is a chronic and disabling condition, caused by a lesion or disease of the somatosensory nervous system, characterized by a systemic inflammatory state. Signs and associated symptoms are rarely recognized, and response to usual analgesic drugs is poor. Antidepressant drugs are first-line agents for the treatment of NP. This narrative review aims to summarize the role of antidepressant drugs in treating NP and their mechanism of action, focusing on the effects on inflammatory cytokines. Main text. Peripheral nerve injury leads to a local inflammatory response and to the disruption of the blood-medullary barrier, allowing the influx of peripheral immune cells into the central nervous system. Antidepressants have antinociceptive effects because they recruit long-term neuronal plasticity. Amitriptyline modulates the inflammatory response due to the reduction of the mRNA of pro-inflammatory cytokines acting as an adenosine agonist and leading to the activation of the A3AR receptor. Through toll-like receptors, local inflammation determines the release of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α) that drives and stimulates the hyperflammation in NP. Nortriptyline has an important antiallodynic effect in NP as it determines the recruitment of norepinephrine in the dorsal root ganglia. By modulating the β2-adrenoreceptors expressed by non-neuronal satellite cells, it inhibits the local production of TNF-α and determines a reduction of NP symptoms. Following the administration of antidepressants, there is a reduction in the production of TNF-α in the brain which in turn transforms the function of the α2-adrenergic receptor from an inhibitor to an activator of the release of norepinephrine. This is important to prevent the development of chronic pain. Conclusion Inflammatory cytokines are the main players in a bidirectional communication between the central and peripheral nervous system and the immune system in NP. Antidepressants have an important role in NP. Further research should explore the interaction between neuroinflammation in NP, the effects of antidepressants and the clinical relevance of this interaction.